2023
DOI: 10.3389/fcvm.2023.1181617
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal hemoglobin trajectories and acute kidney injury in patients undergoing cardiac surgery: a retrospective cohort study

Abstract: ObjectThe purpose of this study was to describe the longitudinal dynamic hemoglobin trajectories in patients undergoing cardiac surgery and to explore whether they provide a broader perspective in predicting AKI compared to traditional threshold values. Additionally, the interaction of red blood cell transfusion was also investigated.MethodsThe MIMIC-IV database was searched to identify patients undergoing cardiac surgery with cardiopulmonary bypass. Group-based trajectory modeling (GBTM) was used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In regard to blood transfusion, preoperative anemia is a risk factor for postoperative AKI, but blood transfusion itself increases the risk of postoperative AKI 55 . Therefore, individualized blood transfusion plans need to be developed based on a patient’s condition 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…In regard to blood transfusion, preoperative anemia is a risk factor for postoperative AKI, but blood transfusion itself increases the risk of postoperative AKI 55 . Therefore, individualized blood transfusion plans need to be developed based on a patient’s condition 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, simply examining the relationship between hemoglobin level and sepsis outcome may ignore the impact of hemoglobin dynamic changes on the outcome. Some studies have shown that the hemoglobin trajectory subgroups are related to the occurrence of acute kidney injury [9,10] , and the uid balance trajectory is also related to sepsis mortality [11] . However, studies on trends of Hb in sepsis patients have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%